Improving the functional and technological properties of minced pork using a proteolytic enzyme - A. A. Semenova; T. G. Kuznetsova; O. A. Seliverstova; M. N. Salikova; M. E. Spirina; Yu. M. Bukhteeva (Теория и практика переработки мяса, 2024)
The use of pork obtained from intensively growing hybrid animals as the main raw material in meat processing, in particular sausage production, is accompanied by undesirable variability of consumer characteristics of sausage products and a decrease in the economic indicators of enterprise performance. The main technological disadvantages of processed pork are reduced water-binding capacity and significant loss of meat fluid, which in practice is usually compensated by the increased use of food additives and non-meat ingredients. The aim of the study was to assess the possibility of targeted improvement of the technological properties of minced pork using a proteolytic enzyme of animal origin. Model samples of minced meat were developed and cured for 24 hours at a temperature of 4 °C. The following control samples were used: minced meat with the addition of 2% edible salt and minced meat with the addition of 2% edible salt and 0.2% sodium bicarbonate. Moreover, 0.0001% chymotrypsin was added to the test samples containing similar curing ingredients. During electrophoretic study, in samples with the enzyme, an increase in low-molecular fractions (20 kDa, 15 kDa and lower) was observed, which indicated the manifestation of proteolytic activity of chymotrypsin in model systems. Enzymatic treatment led to an increase in pH and water-binding capacity. Cooking loss was reduced by 3 to 6 times, compared to Control 1. After cooking, histological studies of model systems showed that the test samples subjected to enzymatic treatment were characterized by a denser arrangement of structural elements, less pronounced cellular components of muscle tissue and the presence of glutin formed as a result of protein breakdown, filling the microcapillaries. Thus, the use of an enzyme preparation provides an opportunity for targeted improvement of the technological properties of pork obtained from intensively growing hybrid animals.